2013
DOI: 10.1063/1.4793650
|View full text |Cite
|
Sign up to set email alerts
|

Electrical modulation of emissivity

Abstract: We demonstrate that it is possible to modulate the thermal emission through an electrical modulation of the emissivity. The basic idea is to design a device where absorption is due to a resonant phenomenon. If the resonance can be electrically controlled, then absorption and, therefore, thermal emission can be controlled. We demonstrate this general concept using THz resonant absorption by surface phonon polaritons coupled through a gold grating. In our device, absorption is mostly due to a surface phonon mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…Progress has also been made in demonstrating dynamic control of thermal radiation through in situ modification of material emissivity. This has been achieved with devices that incorporate phase change materials, which display temperature-dependent emissivities 6 , as well as electronically controlled devices, where injected charges are used to overdampen polariton modes in quantum wells 7 . These results suggest that careful control of both the photonic and electronic structure of metasurfaces could allow for thermal emitters that have continuously variable frequency and directionality control, and that can operate at speeds much faster than typical thermal cycling times, potentially approaching speeds of modern telecommunication devices.…”
mentioning
confidence: 99%
“…Progress has also been made in demonstrating dynamic control of thermal radiation through in situ modification of material emissivity. This has been achieved with devices that incorporate phase change materials, which display temperature-dependent emissivities 6 , as well as electronically controlled devices, where injected charges are used to overdampen polariton modes in quantum wells 7 . These results suggest that careful control of both the photonic and electronic structure of metasurfaces could allow for thermal emitters that have continuously variable frequency and directionality control, and that can operate at speeds much faster than typical thermal cycling times, potentially approaching speeds of modern telecommunication devices.…”
mentioning
confidence: 99%
“…A proof of principle has been reported in Ref. [29] and a very effective source operating up to 600 kHz has been reported [30]. All these developments can be analyzed using Kirchhoff law [31], which expresses the equality of absorptivity and emissivity.…”
Section: Introductionmentioning
confidence: 99%
“…We have further shown that the behaviors given by this very simple case are rather robust, since we can find the same behaviors in very different geometries and for different materials. This paves the way to very interesting possibilities, particularly in semiconductors, in which such ultrathin layers can be easily fabricated, and opens up possibilities in many applications, such as directional perfect absorption [19,28,29] [27], electro-optical modulation [30], and ultrafast thermal emission [16,31].…”
mentioning
confidence: 99%